U.S. Business cycle volatility and banking productivity (2003)
In this paper I address two questions. First, is the fall in the cyclical volatility of U.S. commercial banking productivity a potential candidate to account for the mid-80's fall in U.S. business cycle volatility? Second, does the answer to the previous question change under the presence of financial frictions? The answer to the first question is that the fall in the cyclical volatility of banking productivity contributes significantly only to the volatility fall of the credit cycle. The answer to the second question is that allowing for financial acceleration does not change the results significantly.